2011
DOI: 10.1542/peds.2010-3721
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Behavior Problems of Teen Online Problem-Solving for Adolescent Traumatic Brain Injury

Abstract: Our findings suggest that TOPS contributes to improvements in parent-teen conflict generally and parent and self-reported teen behavior problems for certain subsets of participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
97
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 13 publications
0
97
1
1
Order By: Relevance
“…problem-solving and emotional dysregulation) noted minimal behavioural changes immediately post-intervention [58, 93,98,100,104,105,107]. However there was high participant satisfaction with using tele-practice [93] and greater changes observed in outcome at follow-up [58, 98,100,104,105,107].…”
Section: Telerehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…problem-solving and emotional dysregulation) noted minimal behavioural changes immediately post-intervention [58, 93,98,100,104,105,107]. However there was high participant satisfaction with using tele-practice [93] and greater changes observed in outcome at follow-up [58, 98,100,104,105,107].…”
Section: Telerehabilitationmentioning
confidence: 99%
“…Indeed, telerehabilitation for MANUSCRIPT ACCEPTED -BRAIN INJURY: 02 FEBRUARY 2017 17 people with TBI featured in 38 of the included papers (see Table 2), comprising 2 systematic reviews [39,79], 22 group comparison trials [23][24][25]30,35,52,58,74,77,82,84,[98][99][100][104][105][106][108][109][110][111]113], 9 case series [28,50,80,83,93,97,101,102,107] Importantly, no statistically significant differences were found between the tele-practice and face-to-face intervention delivery methods [39,79].…”
mentioning
confidence: 99%
“…[32][33][34][35]50 In a large randomized controlled trial, we documented improvements on ratings of global executive functioning in older but not younger adolescents. On further analysis, it appears that older teens improved in both behavioral regulation and metacognitive aspects of executive functioning.…”
Section: Discussionmentioning
confidence: 92%
“…21 Problem-solving training has demonstrated promise in various clinical populations [22][23][24][25][26] ; however, it has only been preliminarily explored in pediatric TBI. [27][28][29][30][31][32][33][34] In a small randomized trial of children aged 5 to 17 years (N = 32), findings showed that family-centered online problem-solving therapy improved internalizing behavioral problems after severe TBI. 32 Initial evidence suggests that problem-solving interventions can also be delivered effectively through a web-based portal directly to children with TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation